Evaluation of a new type of titanium mesh cage versus the traditional titanium mesh cage for single-level, anterior cervical corpectomy and fusion - Fengbin, Yu (Springer Berlin Heidelberg, 2013)
STUDY DESIGN: A retrospective review of prospectively collected data in an academic institution. OBJECTIVE: To evaluate the safety and efficacy of a new type of titanium mesh cage (TMC) in single-level, anterior cervical corpectomy and fusion (ACCF). METHODS: Fifty-eight patients consecutive with cervical spondylotic myelopathy (CSM) from cervical degenerative spondylosis and isolated ossification of the posterior longitudinal ligament were treated with a single-level ACCF using either a new type of TMC (28 patients, group A) or the traditional TMC (30 patients, group B). We evaluated the patients for TMC subsidence, cervical lordosis (C2–C7 Cobb and Cobb of fused segments) and fusion status for a minimum of 30 months postoperatively based on spine radiographs. In addition, neurologic outcomes were evaluated using the Japanese Orthopedic Association (JOA) scores. Neck pain was evaluated using a 10-point visual analog scale (VAS). RESULTS: The loss of height of the fused segments was less for group A than for group B (0.8 ± 0.3 vs. 2.8 ± 0.4 mm) (p < 0.01); also, there was a lower rate of severe subsidence (≥3 mm) in group A (4 %, 1/28) than in group B (17 %, 5/30) (p < 0.01). There were no differences in the C2–C7 Cobb and Cobb of fused segments between the groups preoperatively or at final follow-up (p > 0.05), but the Cobb of fused segments immediately postoperative were significantly less for group B than for group A (p < 0.01). All patients, however, had successful fusion (100 %, each). Both groups had marked improvement in the JOA score after operation (p < 0.01), with no significant differences in the JOA recovery ratio (p > 0.05). The postoperative VAS neck pain scores for group A were significantly less than that for group B (p < 0.05); severe subsidence was correlated with neck pain. CONCLUSIONS: The new type of TMC provides comparable clinical results and fusion rates with the traditional TMC for patients undergoing single-level corpectomy. The new design TMC decreases postoperative subsidence (compared to the traditional TMC); the unique design of the new type of TMC matches the vertebral endplate morphology which appears to decrease the severity of subsidence-related neck pain in follow-up.